Risk Assessment of Low-Level Cadmium and Arsenic on the Kidney - Huang, Mingai; Choi, Seong-Jin; Kim, Dong-Won; Kim, Na-Young; Park, Choong-Hee; Yu, Seung-Do; Kim, Dae-Seon; Park, Kyung-Su; Song, Jae-Seok; Kim, Heon; Choi, Byung-Sun; Yu, Il-Je; et al. (TAYLOR & FRANCIS INC, 2009)
Cadmium (Cd) and arsenic (As) are widely distributed in the environment and are known human carcinogens. Several studies reported that chronic exposure to Cd and As produced renal injuries in humans. As one of the mechanisms, oxidative stress was suggested to play a role in the early process of Cd-and/or As-induced tubular damage in the kidney. This study was performed to evaluate the significance of urinary biomarkers, role of oxidative stress, and effect of coexposure to environmental low-level exposure to Cd and/or As in the general population. Urine samples were collected from 290 adults (86 males and 204 females). Urinary concentrations of Cd and As were measured, and kidney biomarkers of toxicity such as beta(2)-microglobulin and N-acetyl-beta-D-glucosaminidase (NAG) activity determined in urine. Urinary malondialdehyde (MDA) and 8-hydroxy-2'-deoxyguanosine (8-OHdG) levels were measured as oxidative stress indices. The mean concentration of Cd was 1.21 mg/L, 0.84 mg/g creatinine, and As was 5.7 mg/L, 3.95 mg/g creatinine in urine. NAG, MDA, and 8-OHdG were positively correlated with both Cd and As in urine. Positive correlations were also observed between NAG and oxidative indices. The effects of coexposure to Cd and As on biomarkers are more pronounced than for exposure to each metal alone. These findings suggest that chronic exposure to low levels of Cd and/or As might produce tubular damage in the kidney through oxidative stress in humans.
Keywords: OXIDATIVE-STRESS; LIPID-PEROXIDATION; RENAL DYSFUNCTION; CHRONIC EXPOSURE; URINARY CADMIUM; DNA-DAMAGE; POPULATION; WORKERS; METALLOTHIONEIN; WOMEN